Bessel_DMD: the numerical code based on the scalar Fresnel–Kirchhoff integration to calculate the diffraction and bessel-like beam by using the DMD - Pei, Ting-Han (2024)
We provide numerical software based on the MATLAB programming language to study the Bessel-like beams generated by special instruments such as DMD. The calculations are based on the scalar Fresnel–Kirchhoff integration within the scope of Fourier Optics. This analysis is particularly important because the addition of higher-order Bessel terms may produce additional unexpected experimental results in some applications. We emphasize the seldom-mentioned imaging characteristic on the lens, where the central point is shifted, and provide numerical software to understand the expression of the Bessel-like function obtained from important theoretical derivation. It also benefits to verify and explain the experimental results.